Rancang Bangun Dashboard Monitoring Kinerja Petugas PPSU Pada Kelurahan Pisangan Baru - Dian Gustina; Ahmad Rosadi; Febrianne Ardianti (Fakultas Teknik Universitas Persada Indonesia YAI, 2023)
Kelurahan is one of the most important parts of service for the community. One of themandatory services provided by the kelurahan is service to public facilities andinfrastructure, for that the kelurahan has special officers who handle these problems,namely PPSU officers or orange troops. PPSU is a janitor who works under the controlof the kelurahan level. In the presentation of monitoring information there is no mediathat helps make it easier for Pisangan Baru village employees to see the performanceof PPSU officers. Therefore we need a system that can monitor and present visualinformation about the performance of PPSU officers called the Dashboard.